Teleradiologie - Weisser, Gerald; Walz, Michael (Der Diabetologe, 2012)
Digitization of the imaging modalities and the connectivity through the Internet has rapidly developed over the last 15 years. In Germany quite a few regional teleradiology networks exist, nevertheless, many of them are not interoperable due to the lack of an international or national teleradiology standard. Therefore, a range of different techniques are in use for the realization of teleradiology networks. Upon setup of a new teleradiology connection the desired use scenarios, necessary connections to existing networks and other requirements must be analyzed to find a cost-effective and suitable solution. Data security aspects, legal aspects and refunding must also be taken into account. Teleconsultation and teleguided examinations are currently part of the clinical routine in many German regions ensuring a high quality and affordable medical service.
Gesehen am 16.07.2018